Application of narrative education in curriculum ideology and politics focusing on job competencies in clinical teaching of nursing students (叙事教育在以岗位胜任力为核心的全日制护生思政教育带教模式中的应用研究) - DENG Lijun (邓丽君); TANG Biying (唐碧英); YU Qiuhua (余秋花); LIU Yuanyuan (刘圆圆); HUANG Tianwen (黄天雯) (Association of Integrative Nursing, 2023)
Objective To investigate the application value of narrative education in curriculum ideology and politics focusing on job competencies in clinical teaching of nursing students. Methods Totally 61 nursing students who participated in the clinical internship between July 2021 and May 2022 were included as the control group, and curriculum ideology and politics focusing on job competencies was adopted in the clinical teaching. Another 59 nursing students who participated in the clinical internship between June 2022 and May 2023 were included as the control group, and a combination of curriculum ideology and politics focusing on job competencies and narrative education was performed in the clinical teaching. The narrative education capacity of nursing students in the observation group was evaluated before and after internship. The psychological traits assessment score, outcomes of assessment of theoretical knowledge and practical skills, nursing students' attitude goals evaluated by clinical teachers, and nursing students' satisfaction with clinical teaching were compared between two groups. Results The scores of narrative skills, the Jefferson Scale of Empathy-Health Professionals and humanistic care ability of students in the observation were increased significantly after internship (P＜0. 01). The psychological traits assessment score in the observation group was higher than that in the control group (P＜0. 01). Students in the observation group achieved higher outcomes of assessment of theoretical knowledge and practical skills compared with those in the control group (P＜0. 05). The score of assessment on nursing students' attitude goals in the observation group was higher than that in the control group (P＜0. 01). The score of nursing students' satisfaction in the in the observation group was higher than that in the control group (P＜0. 05). Conclusion The combination of narrative education and curriculum ideology and politics focusing on job competencies is effective to enhance the narrative education capacity and psychological traits of nursing students, improve the quality of clinical teaching, and develop the excellent teaching culture of inheritance, innovation and development. (目的 探讨叙事教育在以岗位胜任力为核心的全日制护生思政教育带教模式中的应用效果。方法 将2021年7月-2022年5月在骨科临床实习的61名本科全日制护生设为对照组, 将2022年7月-2023年5月在骨科临床实习的59名本科全日制护生设为观察组。对照组实施以岗位胜任力为核心的思政教育带教模式, 观察组在以岗位胜任力为核心的思政教育带教模式的基础上增加叙事教育。评价观察组护生叙事教育能力; 对比两组护生心理特质评分, 以及护生出科时理论和技能考核成绩; 评价带教老师对护生的态度目标, 以及护生对教学工作的满意度。结果 观察组护生医学叙事能力、杰弗逊共情能力、人文关怀能力评价指标得分出科时均高于入科时, 差异有统计学意义(P＜0. 01)。观察组护生心理特质得分高于对照组, 差异有统计学意义(P＜0. 01)。观察组护生出科理论成绩、技能成绩均高于对照组, 差异有统计学意义(P＜0. 05)。观察组护生态度目标得分高于对照组, 差异有统计学意义(P＜0. 01)。观察组护生对教学满意度评分高于对照组, 差异有统计学意义(P＜0. 05)。结论 叙事教育在以岗位胜任力为核心的全日制护生思政教育带教模式中的应用, 提高了护生的叙事教育能力、心理特质、教学质量及教学满意度, 形成"传承、创新、发展"的优秀教学文化, 达到高质量高水平教学。)